2005
DOI: 10.1369/jhc.4b6414.2005
|View full text |Cite
|
Sign up to set email alerts
|

Another Small Supernumerary Marker Chromosome (sSMC) Derived from Chromosome 2: Towards a Genotype/Phenotype Correlation

Abstract: Here we report a prenatally detected small supernumerary marker chromosome (sSMC) derived from chromosome 2 as demonstrated by cenM-FISH (centromere-specific multicolor fluorescence in situ hybridization). By application of a recently described subcentromere-specific probe set (subcenM-FISH) for chromosome 2, the presence of a small partial trisomy due to a karyotype 47,XX, + r(2)(::p11.1->q11.2::) was demonstrated. Including this case, a total of 11 patients with sSMC(2) are described throughout the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
(6 reference statements)
2
12
1
1
Order By: Relevance
“…We did not find any other publications reporting patients being trisomic for exactly the same region of chromosome 2 (3)(4)(5)(6)(7)(8)(9)(10). The duplication detected in our present case contains even less genetic material than those previously reported.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We did not find any other publications reporting patients being trisomic for exactly the same region of chromosome 2 (3)(4)(5)(6)(7)(8)(9)(10). The duplication detected in our present case contains even less genetic material than those previously reported.…”
Section: Discussioncontrasting
confidence: 67%
“…However, if there is any correlation with the renal symptoms described in (4) is impossible to conclude. A review of previously published cases with constitutional duplication of region 2p11.2→q11.2 demonstrated variability between patients harboring and lacking clinical findings (3,4,5,6,7,8,9,10). The duplication detected in our present case contains even less genetic material than those previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 6 (see Table 1) presented a mosaicism with an extra marker chromosome 2 composed of euchromatic material derived from centromerenear sequence 2p11.2 to sequence 2q13. Clinical consequences of this very rare aberration (a dozen of cases have been reported) are described as inconsistent, but Mrasek et al previously observed an association between the presence of sequence 2p11.2 and clinical abnormalities [12]. Indeed this patient presented behavior problems and learning troubles associated with an attention-deficit hyperactivity disorder.…”
Section: Discussionmentioning
confidence: 91%
“…To date, 17 sSMCs(2) with known clinical significance have been described. None of the SMCs(2) reported in the literature contained the chromosome region present in the SMC(2) in patient RS (Plattner et al 1993;Petit and Fryns 1997;Ostroverkhova et al 1999;Villa et al 2001;Giardino et al 2002;Lasan et al 2003;Starke et al 2003;Guancialli-Franci et al 2004;Mrasek et al 2005). In addition, a patient with trisomy 2q35-q37 (due to insertion of 2q material into 17q25) had a few similar clinical symptoms, such as psychomotor retardation, speech delay, short neck and fingers (found in the presented case), suggesting that they are consequences of the additional copy of this region of chromosome 2 (Fritz et al 1999).…”
Section: Discussionmentioning
confidence: 99%